2021
DOI: 10.1024/1422-4917/a000793
|View full text |Cite
|
Sign up to set email alerts
|

Elektrokonvulsionstherapie im Kindes- und Jugendalter

Abstract: Zusammenfassung. Hintergrund und Zielsetzung: Die Elektrokonvulsionstherapie (EKT) ist ein hoch wirksames und in der Erwachsenenpsychiatrie gut untersuchtes Therapieverfahren, das gerade bei schwerwiegenden depressiven und psychotischen Erkrankungen erfolgreich eingesetzt wird. Obwohl schwere Krankheitsverläufe auch im kinder- und jugendpsychiatrischen Bereich vorkommen, erfolgt ein Einsatz der EKT hier deutlich seltener. Dies liegt womöglich auch daran, dass kaum systematisch erhobene Daten zur Anwendung, Wir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…This study provided convincing evidence that ECT is effective for adolescents with depression and suicidal ideation, consistent with previous literature. A retrospective analysis of 29 adolescent patients (<18 years; 13 with depressive disorders, 6 with catatonia, and 8 with schizophrenia) treated with ECT at 3 German research centers 29 found that ECT improved outcomes in those who did not respond well to drugs. Moreover, ECT had no serious adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…This study provided convincing evidence that ECT is effective for adolescents with depression and suicidal ideation, consistent with previous literature. A retrospective analysis of 29 adolescent patients (<18 years; 13 with depressive disorders, 6 with catatonia, and 8 with schizophrenia) treated with ECT at 3 German research centers 29 found that ECT improved outcomes in those who did not respond well to drugs. Moreover, ECT had no serious adverse effects.…”
Section: Discussionmentioning
confidence: 99%
“…The study was approved by the respective institutional review boards of the 3 institutions. Twenty nine of the 32 included patients reported here have already been published in German 30 …”
Section: Methodsmentioning
confidence: 99%
“…A recent literature research yielded only 24 articles on ECT in child and adolescent psychiatry—aside from individual case reports (Table 1). 12,14,22,30 Altogether, 1096 cases were published internationally. No meta-analyses or randomized controlled studies were found.…”
Section: Review Of Existing Literaturementioning
confidence: 99%